Kemampuan Kayu Secang (Caesalpinia sappan L.) dalam Menurunkan Bakteri Coliform pada Air Minum sebagai Upaya Penanggulangan Kasus Diare - Kasim, Khiki Purnawati; Stientje, Stientje; Haerani, Haerani (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Diarrhea has become a  global health problem due tolack of access to clean and safe water.  According to the World Health Organization (WHO), diarrhea causes more than 500,000 child deaths every  year, especially in countries with limited access to sanitation and health services. So it is necessary to anticipate through several concrete steps, one of which is by utilizing natural resources that are useful as anti-microbials such as secang wood. The aim of  this research is to determine the ability of secang wood (Caesalpinia sappan L.) to reduce Coliform bacteria in drinking water as an effort to treat cases of diarrhea using a quasi experimental research method on laboratory scale using 1 gram of secang wood in 1 liter of drinking water for 12 hours with sample variations in boiled drinking water,  refill drinking water from 5 sources, and controls. The result of the research show that the  addition of  secang wood to boiled drinking water refilled drinking water can kill Coliform bacteria 100%, from 240 CFU/100 ml to 0 CFU/ 100 ml and statistical show that there is a significant difference (p value= 0,025) in the ability of secang wood in reduces coliform. For controls there is no significant difference(p value= 0,025). The addition of seppan wood to boiled drinking water and refill drinking water can reduce coliform bacteria in accordance with the requirements of RI Minister of Health  No. 2 of 2023. So it is recommended for the community to utilize seppan wood in drinking water as an effort to prevent diarrhea. Keywords: Coliforms; drinking water; sappan wood